2016
DOI: 10.3171/2015.1.jns14681
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal anterior cingulotomy and anterior capsulotomy for severe, refractory obsessive-compulsive disorder: a systematic review of observational studies

Abstract: OBJECT The object of this study was to perform a systematic review, according to Preferred Reporting Items of Systematic reviews and Meta-Analyses (PRISMA) and Agency for Healthcare Research and Quality (AHRQ) guidelines, of the clinical efficacy and adverse effect profile of dorsal anterior cingulotomy compared with anterior capsulotomy for the treatment of severe, refractory obsessive-compulsive disorder (OCD). METHODS The authors included studies comparing objective clinical measures before and after cingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 28 publications
3
96
1
3
Order By: Relevance
“…Anterior capsulotomy is a stereotactic procedure in which the reciprocal projections between the orbitofrontal cortex and the thalamus are lesioned. This procedure has been shown to alleviate obsessive symptoms and anxiety and demonstrates the relevance of the fibers projecting through the ALIC in the control of emotion and behavior. Radiofrequency ablation of the anterior cingulate has also shown the ability to alleviate symptoms in OCD as well as pain in chronic cancer and noncancer pain .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Anterior capsulotomy is a stereotactic procedure in which the reciprocal projections between the orbitofrontal cortex and the thalamus are lesioned. This procedure has been shown to alleviate obsessive symptoms and anxiety and demonstrates the relevance of the fibers projecting through the ALIC in the control of emotion and behavior. Radiofrequency ablation of the anterior cingulate has also shown the ability to alleviate symptoms in OCD as well as pain in chronic cancer and noncancer pain .…”
Section: Discussionmentioning
confidence: 89%
“…This procedure has been shown to alleviate obsessive symptoms and anxiety and demonstrates the relevance of the fibers projecting through the ALIC in the control of emotion and behavior. Radiofrequency ablation of the anterior cingulate has also shown the ability to alleviate symptoms in OCD as well as pain in chronic cancer and noncancer pain . Although these ablative procedures can be effective, there are significant concerns for cognitive changes at follow‐up and the risk for deterioration of executive function …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A recent report described a 47% full and 22% partial response to cingulotomy and limbic leucotomy for severe OCD 45. Another comparison of anterior capsulotomy to cingulotomy found a comparable response rate of 54% and 41%, respectively 46. A recent retrospective comparison of capsulotomy to VC/VS DBS (thus comparing interventions in the same region) found a significant advantage in Yale-Brown Obsessive Compulsive Scale (YBOCS) reduction (51% vs 40%) and remission rate favouring capsulotomy 47…”
Section: Current State Of Knowledgementioning
confidence: 99%
“…For the open procedures, active versus sham comparisons of outcome are not feasible. However, unblinded, long-term, prospective studies have demonstrated response rates as high as 69% for intractable OCD 6 and 75% for TRD 7 for anterior cingulotomy and/or subcaudate tractotomy and 54% for anterior capsulotomy for intractable OCD 8 . Ablative limbic system surgery is not currently typically used to treat any other psychiatric disorders.…”
Section: Neurotherapeutic Interventionsmentioning
confidence: 99%